2014
DOI: 10.3233/jad-140435
|View full text |Cite
|
Sign up to set email alerts
|

Needs of People with Severe Dementia at the End-of-Life: A Systematic Review

Abstract: This systematic review shows the paucity of empirical findings on the needs of people with severe dementia. The structured presentation of thematic categories points to a clearer delineation of these needs. Thus, this overview emphasizes the topics for future research and can likewise serve as an orientation for care provision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 11 publications
0
35
0
Order By: Relevance
“…These elements are represented by the two EAPC Delphi study domains found most important by experts [4] and are also consistently seen as attributes of a good death [23]. In a systematic review on needs of people with advanced dementia, Perrar et al [24] additionally found environmental and supportive needs, relating to more practical needs such as the physical environment [25] and which should not be neglected as a means to bring comfort for people with advanced dementia. Also, an optimal approach for people with dementia more generally combines availability of medical care in the background with a frontline of social and human approach by dedicated nursing staff and volunteers.…”
Section: Discussionmentioning
confidence: 99%
“…These elements are represented by the two EAPC Delphi study domains found most important by experts [4] and are also consistently seen as attributes of a good death [23]. In a systematic review on needs of people with advanced dementia, Perrar et al [24] additionally found environmental and supportive needs, relating to more practical needs such as the physical environment [25] and which should not be neglected as a means to bring comfort for people with advanced dementia. Also, an optimal approach for people with dementia more generally combines availability of medical care in the background with a frontline of social and human approach by dedicated nursing staff and volunteers.…”
Section: Discussionmentioning
confidence: 99%
“…The national plan recommended psychiatric hospitals and nursing homes as a treatment option for people with moderate or severe challenging behaviour in dementia (Ministry of Health, Labour, and Welfare, ), while community‐based mental health services have been designated as the main method for addressing challenging behaviour in other countries. Most research examining palliative care for people with dementia has focused on end‐of‐life care in residential settings (van der Steen, ; Perrar et al ., ). There has been no examination of professional caregivers' perspectives regarding palliative care for dementia in community care settings.…”
Section: Introductionmentioning
confidence: 97%
“…Palliative care for persons with dementia is often complex, and heterogeneous care needs may arise (Perrar, Schmidt, Eisenmann, Cremer, & Voltz, 2015), especially in the advanced stages (Hendriks, Smalbrugge, Galindo-Garre, Hertogh, & van der Steen, 2015;Mitchell et al, 2009). Lacking skills and knowledge among nursing staff may adversely affect the quality of palliative care (Erel, Marcus, & Dekeyser-Ganz, 2017;Mitchell et al, 2009;Robinson et al, 2014).…”
mentioning
confidence: 99%